Optimizing Potassium Fertilization Combined with Calcium–Magnesium Phosphate Fertilizer Mitigates Rice Cadmium Accumulation: A Multi-Site Field Trial - Qiying Zhang; Weijian Wu; Yingyue Zhao; Xiaoyu Tan; Yang Yang; Qingru Zeng; Xiao Deng (Agriculture)
Alkaline fertilizers demonstrate significant potential in mitigating rice cadmium (Cd) accumulation, yet the combined effects of calcium–magnesium phosphate (CMP) with potassium (K) fertilizer types and split application strategies remain unclear. Through multi-site field trials in Cd-contaminated paddy soils, we evaluated split applications of K2CO3, K2SO4, and K2SiO3 at tillering and booting stages following basal CMP amendment. Optimized K regimes reduced brown rice Cd concentrations (up to 89% reduction) compared to conventional fertilization. Notably, at the CF site, split K2SiO3 application (TB-K2SiO3) and single tillering-stage K2SO4 (T-K2SO4) achieved brown rice Cd levels of 0.13 mg/kg, complying with China’s food safety standard (≤0.20 mg/kg), thereby eliminating non-carcinogenic risks. Mechanistically, TB-K2SiO3 enhanced soil pH by 0.21 units and increased available K (AK) by 50.26% and available Si (ASi) by 21.35% while reducing Cd bioavailability by 43.55% compared to non-split K2SiO3. In contrast, T-K2SO4 elevated sulfate-driven Cd immobilization. Structural equation modeling prioritized soil available Cd, root Cd, and antagonistic effects of AK and ASi as dominant factors governing Cd accumulation. The integration of CMP with split K2SiO3 application at the tillering and booting stages or single K2SO4 application at the tillering stage ensures safe rice production in Cd-contaminated soils, offering scalable remediation strategies for paddy ecosystems.